Antibacterial Profile of Verbascum Speciosum Against Bacteria and Fungi Strains - Najat Alahmer; Esadawi Abuneeza; Mohamed Alshriaf; Eltawaty, Salwa (AlQalam Journal of Medical and Applied Sciences, 2025)
The present study aimed to evaluate the antibacterial potential of Verbascum speciosum leaf extract against selected bacterial isolates. Verbascum species are known for their medicinal properties, attributed to their bioactive phytochemical components that exhibit antimicrobial, antifungal, and antiviral effects. The leaves of Verbascum speciosum were collected from Fethiye, Turkey, and subjected to ethanol 60% extraction. The activity of the extract was tested using the agar disc diffusion method against four standard Gram-negative bacteria (E.coli ATCC 25922, Enterobacter aerogenes ATCC 13048, Pseudomonas fluorescens DSMZ 50071, and Klebsiella pneumoniae ATCC 7544), and three Gram-positive bacteria (Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis DSMZ 20044, and Enterococcus faecalis ATCC 29212). Antibiotic susceptibility testing was also conducted using standard antibiotics (Vancomycin, Ceftazidime, Meropenem, Ofloxacin, and Gentamicin) to compare antibacterial efficacy. Results indicated that only Enterococcus faecalis ATCC 29212 exhibited sensitivity to the Verbascum speciosum extract at a concentration of 10µg, with an inhibition zone of 7 ± 0.1 mm. No inhibitory effects were observed against other tested bacteria. In contrast, antibiotic testing revealed varying degrees of sensitivity among bacterial isolates. Meropenem showed the strongest inhibitory effect across most strains. MIC testing further confirmed limited antimicrobial activity of the plant extract against Enterococcus faecalis. Statistical analysis showed no significant differences in antibacterial effectiveness across different plant extract concentrations, and significant differences between antibiotics and the extract's effectiveness (P-v >0.05). These findings suggest that while Verbascum speciosum contains bioactive compounds, its antibacterial potency is limited under the tested conditions, where it exhibits selective and limited antibacterial activity, primarily against Enterococcus faecalis. Further studies may be necessary to explore enhanced extraction methods or synergistic effects with conventional antibiotics.